Prostate cancer : biochemistry, molecular biology and genetics - Tindall, Donald J. (Protein Reviews, 2013)
Prostate cancer is the most frequently diagnosed non-cutaneous malignancy in men, and the second leading cause of male cancer-related mortality in the United States.  The last decade has seen unprecedented progress in the detection, prognosis, treatment and prevention of prostate cancer. These advances have been driven largely by an increased understanding of the underlying biochemistry, molecular biology and genetics of the disease. New cell and animal models have been developed that recapitulate the natural progression of prostate cancer. New technologies have allowed scientists to view in detail the genomic, proteomic, metabolomics and other -omic universe of cancer cells and tissues. This has resulted in a greater understanding of the pathophysiology of the disease.